2019
DOI: 10.1002/mrm.27739
|View full text |Cite
|
Sign up to set email alerts
|

NMR quantification of lactate production and efflux and glutamate fractional enrichment in living human prostate biopsies cultured with [1,6‐13C2]glucose

Abstract: Purpose Image‐guided prostate biopsies are routinely acquired in the diagnosis and treatment monitoring of prostate cancer, yielding useful tissue for identifying metabolic biomarkers and therapeutic targets. We developed an optimized biopsy tissue culture protocol in combination with [1,6‐13C2]glucose labeling and quantitative high‐resolution NMR to measure glycolysis and tricarboxcylic acid (TCA) cycle activity in freshly acquired living human prostate biopsies. Methods We acquired 34 MRI‐ultrasound fusion‐g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…The re-balancing of the levels of TCA cycle intermediates and enzymes in the post-treatment mice is therefore a metabolic reflection of the reduced tumor size observed in mice treated with tTF-pHLIP (Figures A and E). Energy disruption associated with tumor growth also presents with rewired glycolysis, also known as Warburg effect, and is the most important metabolic alteration which rapidly consumes glucose and secret abundant lactate . Our current study observed an elevated level of lactate in plasma, urine, and liver in tumor-bearing mice, which were consistent with the Warburg effect of tumors.…”
Section: Discussionsupporting
confidence: 81%
“…The re-balancing of the levels of TCA cycle intermediates and enzymes in the post-treatment mice is therefore a metabolic reflection of the reduced tumor size observed in mice treated with tTF-pHLIP (Figures A and E). Energy disruption associated with tumor growth also presents with rewired glycolysis, also known as Warburg effect, and is the most important metabolic alteration which rapidly consumes glucose and secret abundant lactate . Our current study observed an elevated level of lactate in plasma, urine, and liver in tumor-bearing mice, which were consistent with the Warburg effect of tumors.…”
Section: Discussionsupporting
confidence: 81%
“…Increased signals of lactate, commonly observed for tumors because of high glycolysis (i.e., Warburg effect), are seen in 1 H MR spectra of PCa tissue in vitro [ 49 , 76 ], but these signals appear to be under the detection limit (~1.5 mM) of in vivo 3T MRSI of tumor lesions in the prostate recorded at TE = 144 ms [ 77 ]. Furthermore, the methyl lactate signal, if present, is easily obscured by signals of lipids resonating at a similar chemical shift or suppressed together with these signals, a common procedure embedded in most acquisition sequences.…”
Section: H Mrsi Of the Prostatementioning
confidence: 99%
“…These improvements range from early, slow spinning schemes aimed at better preserving tissue architecture during HRMAS analysis to further subsequent pathology evaluations, 20 to recently reported schemes for more comprehensively defining disease metabolomic profiles by diffusion‐filtered 93 and heteronuclear single quantum correlation (HSQC) 94 spectroscopy. HRMAS NMR has also been developed to validate patient‐derived tumor models in a hypoxic microenvironment by evaluating functional, genomic, and metabolomics data, 43 as well as to quantify lactate production from living human prostate biopsies cultured with [1,6‐ 13 C]glucose 95 …”
Section: Recent Advancements In Hrmas Nmrmentioning
confidence: 99%